Konstruksi Yuridis Politik Legislasi DPD Pasca Putusan Mahkamah Konstitusi Nomor 92/PUU-X/2012 - Ria Casmi Arrsa (Jurnal Konstitusi, 2015)
The position of Regional Representative Council in the context of the implementation of the legislative function has an important role in order to create the principle of checks and balances between state institutions which include the House of Representatives and the President. Contextually Constitutional Court Decision No. 92/PUU-X/2012 reinforce the DPD position both in terms of national legislation program planning, delivery of opinions, views, list of inventory issues,  and discussion of a draft law. Much progress has been achieved but in the political realm seems legislative authority of the DPD is still not perfect when not reached the stage of deciding to join a draft law being discussed. In order to strengthen    DPD as part of regional representation, the amendments to the Constitution of  1945 was important to conduct state institutional arrangement holistically and comprehensively.